2006
DOI: 10.1103/physrevb.73.155103
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Wigner crystallization in quasi-low-dimensional solids

Abstract: The crystallization of electrons in quasi low-dimensional solids is studied in a model which retains the full three-dimensional nature of the Coulomb interactions. We show that restricting the electron motion to layers (or chains) gives rise to a rich sequence of structural transitions upon varying the particle density. In addition, the concurrence of low-dimensional electron motion and isotropic Coulomb interactions leads to a sizeable stabilization of the Wigner crystal, which could be one of the mechanisms … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
(74 reference statements)
2
12
0
Order By: Relevance
“…The zero-field phase diagram as a function of temperature and the ratio δ between the exchange and dipolar constants (see eq. (1)) has been focused on [6][7][8][9][10][11][12][13][14][15][16][17][18]. The dipolar interaction leads to the antiferromagnetic (AF) ground state [7], while the Ising ferromagnetic exchange interaction causes the ferromagnetic ground state.…”
Section: Introductionmentioning
confidence: 99%
“…The zero-field phase diagram as a function of temperature and the ratio δ between the exchange and dipolar constants (see eq. (1)) has been focused on [6][7][8][9][10][11][12][13][14][15][16][17][18]. The dipolar interaction leads to the antiferromagnetic (AF) ground state [7], while the Ising ferromagnetic exchange interaction causes the ferromagnetic ground state.…”
Section: Introductionmentioning
confidence: 99%
“…The Wigner crystallization in this material is likely due to the suppression of kinematic energy in the narrow band. Recent theoretical work on the jellium model [18] has shown that Wigner crystallization is enhanced in low- dimensional solids because the kinetic energy is suppressed by this dimensionality, and consequently the relative Coulomb effect is emphasized. According to this theory, DI-DCNQI 2 Ag could be a Wigner crystal.…”
mentioning
confidence: 99%
“…In spite of this difficulty, the two-dimensional (2D) dipolar Heisenberg model with uniaxial anisotropy (see Eq. (1)) has been intensively studied for understanding ultrathin-film magnetism theoretically and computationally [6][7][8][9][10][11][12][13][14][15][16][17][18][19], as well as the 2D dipolar Ising ferromagnet [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Especially, the η-T (uniaxial anisotropy vs. temperature) phase diagram of the model (1) at zero field (H = 0) has been focused on, while the phase diagrams for finite fields are almost unexplored.…”
Section: Introductionmentioning
confidence: 99%